Patterns of local species richness and their associations with functional traits in a 60‐ha tropical forest dynamics plot. Issue 4 (12th April 2019) - Zang, Lipeng; Xu, Han; Lin, Mingxian; Zang, Runguo
Abstract: Understanding the underlying mechanisms of diversity maintenance in tropics remains a challenge for ecologists. To reveal the underlying mechanism from a plant‐eye‐view perspective, we examined the patterns of local species richness which was defined as the number of species around individuals of a target species within circles of different radii and their correlations with major plant functional traits in a tropical montane rainforest. In 2012, we established a 60‐ha forest dynamics plot (FDP) in tropical montane rainforest on Hainan Island, China. In 2013, we measured eight functional traits (specific leaf area [SLA], leaf dry matter content [LDMC], wood density, potential maximum height, leaf carbon content [LCC], leaf nitrogen content [LNC], leaf phosphorus content [LPC], and leaf potassium content) of all the species in the FDP. Based on all the mapped individuals that had a diameter at breast height ≥10 cm, we utilized individual species–area relationships function (ISARs ( r )) combined with the heterogeneous Poisson null model to quantify the patterns of local species richness at scales from 1 to 50 m. Regression analysis was used to determine which functional traits could influence the local diversity pattern. Results showed that the 123 ISARs ( r ) curves were relatively similar and no species seemed to be extremely higher or lower than the average of all the ISARs ( r ) curves. The percentage of species that behaved predominantly as accumulators or repellers or neutrally was 42.23%, 13.82%, and 43.9% at scale of <30 m, respectively. But at scales ≥30 m, more than 70% of all species behaved neutrally suggesting that facilitative interactions probably occurred when neighborhoods were <30 m apart. Among the eight measured traits, the SLA, LNC, and LPC were negatively associated with local species richness. Our results indicated that (1) the spatial community structure was not controlled by key species; (2) facilitative interactions played an important role in local diversity maintenance; (3) species with conservative functional trait syndromes were more likely to have relatively high local species richness in the tropical montane rainforest on Hainan Island, China.